Future fertility in low fertility countries - Mills, MC; Abbasi-Shavazi, M; Adsera, A; Van Bavel, J; Berghammer, C; Choe, MK; Frejka, T; Leridon, H; Morgan, SP; Rindfuss, RR; Rosero-Bixby, L; Rotkirch, A; et al. (Oxford University Press, 2014)
Chapter 3 is the first of six that present a comprehensive science-based assessment of what we know today about the drivers of future fertility, mortality, migration, and education. This chapter concerns countries with currently low fertility. It presents and justifies assumptions for future fertility trajectories based on an overview of recent fertility changes in major low-fertility regions, a discussion of theoretical arguments, a review of factors contributing to fertility change and variation during the late phases of demographic transition, a global survey of experts, and an invited meeting of experts. The survey contains 184 expert assessments with forecasts of period total fertility rates in 2030 and 2050, and substantive assessments of the validity and potential impact on fertility of 46 possible fertility-influencing factors. Invited experts participating in a meeting in Vienna in December 2011 helped transform these survey results into the scenarios that informed the projections reported in this book.